Imagery in football - Munroe-Chandler, K.; Guerrero, M. (Football Psychology - From Theory to Practice, 2019)
Imagery is a popular mental skill used by athletes. This is evident in the growing popularity of brain-training sport-related apps like Nike Pro Genius - an app designed specifically for football players and dedicated to teaching players various mental skills, including imagery. The purpose of this chapter is to discuss and present theoretical and empirical work of imagery as it pertains to the sport of football. The chapter is divided into six main sections. The first section reviews the conceptualization of imagery and theories and models of imagery. In the second section, popular inventories used to assess imagery ability and imagery frequency are discussed, such as the Movement Imagery Questionnaire-3 (Williams et al., 2012), the Sport Imagery Ability Questionnaire (Williams & Cumming, 2011), and the Sport Imagery Questionnaire (Hall, Mack, Paivio, & Hausenblas, 1998). The third section summarizes the existing body of research on imagery within sport. Specifically, individual characteristics consistently shown to influence imagery ability and imagery use are presented, followed by a brief overview of emerging individual characteristics, namely, narcissism, emotion regulation, and goal orientation. The fourth section highlights empirical evidence on the effectiveness of cognitive and motivational uses of imagery in football. The fifth section oudines applied recommendations for coaches and/or practitioners, and discusses two techniques (i.e. layered stimulus response training and imagery scripts) known to help athletes improve their imagery ability. Finally, the sixth section presents avenues for future research.